ANALISA KINERJA PELAYANAN PEMBUATAN KETERANGAN TIDAK MAMPU PADA KANTOR DESA SEPUH GEMBOL KECAMATAN WONOMERTO KABUPATEN PROBOLINGGO - Marsinem . (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2019)
The purpose of this study was to find out how the service performance of making Certificate of Inadequacy at the Sepuh Gembol Village Office in Wonomerto District, Probolinggo Regency. The results of the study state that public services in the making of Not Able Certificate (SKTM) at the Sepuh Gembol Village Office in Wonomerto Sub-District can be said to have materialized well. This can be seen from the indicators in public services, namely, service procedures, service requirements, service time, service costs, service products, facilities / infrastructure and competency of service providers where all of these indicators are in good category. Employee performance in the preparation of the Not Available Certificate (SKTM) has so far been implemented well.